AUDIODESCRIÇÃO SEM PUDORES: ACESSIBILIDADE APLICADA A CENAS ERÓTICAS E SENSUAIS DO FILME PRAIA DO FUTURO - Villela, Lucinéa Marcelino (UNICAMP. Programa de Pós-Graduação em Linguística Aplicada do Instituto de Estudos da Linguagem (IEL), 2017)
ABSTRACT The aim of this paper is to present the challenges encountered during the elaboration of scripts for ADs in scenes of Brazilian movies, which have erotic situations played by its main characters. We will study the case of two scenes of the movie Future Beach (directed by Karim Aïnouz, 2014). The work is divided into two initial parts with the presentation of theoretical content covering the themes of obscenity and eroticism in the area of audiovisual translation and over some fundamental concepts related to audio description. In the third part, we will show the AD case study of two erotic and sensual scenes of the movie Future Beach and conclude with some reflections about the challenges of the AD process.

RESUMO O objetivo deste artigo é apresentar os desafios encontrados na elaboração de roteiro de ADs para cenas de filmes brasileiros que possuem situações de erotismo vivenciadas pelos seus protagonistas. Faremos um estudo de caso de duas cenas do filme Praia do Futuro (dirigido por Karim Aïnouz, 2014). O artigo está dividido em duas partes iniciais, com apresentação de conteúdo teórico sobre as temáticas da obscenidade e do erotismo na área de tradução audiovisual, e alguns conceitos fundamentais sobre audiodescrição. Na terceira parte, apresentaremos o estudo de caso da AD de duas cenas eróticas e sensuais do filme Praia do Futuro e, por último, concluiremos com algumas reflexões sobre os desafios do processo de AD.
SHAMELESS AUDIO DESCRIPTION: ACCESSIBILITY APPLIED TO EROTIC SCENES OF THE MOVIE FUTURE BEACH
Keywords: audio description; audiovisual translation; Future Beach; audiodescrição; Praia do Futuro; tradução audiovisual